Genetic Diversity and Phylogenetic Relationships of Seven Dairy Goat Breeds in Yogyakarta and Central Java Based on Cytochrome B Gene - Mathew Mgogo; Dyah Maharani; Diah Tri Widayati; Alek Ibrahim (Buletin Peternakan, 2026)
Indonesia is endowed with many goat breeds, which include meat-type, dual-purpose, and dairy goats. Studies show that some breeds of goat, including dairy and meat goats in Indonesia, are at risk of extinction, while the level of risk of extinction for others is not yet known. This study was conducted to explore the genetic diversity and phylogenetic relationship of seven goat breeds found in Yogyakarta and Central Java, which included Saanen, British Alpine, Bligon, Anglo Nubian, Toggenburg, Nigerian dwarf, and the Crossbreed of Anglo Nubian with PE. DNA was extracted from blood samples of 31 goats. Partial sequences of the cytochrome b gene from mtDNA with 430 bp, were amplified by using PCR with forward primer 5’-CAACATCCGAAAGACCCACC-3’ and reverse primer 5’-AACAGGATCGAACAACCCCA-3’. The sequenced results were then aligned with 4 reference sequences from GenBank (D84201.1, AB004074.1, NC_005044.2, and KY564254.1) by using MEGA 11 software. NJT constructed in MEGA 11 showed two main clades; the first main clade contains Saanen, British Alpine, Bligon, Anglo Nubian, Toggenburg, and Crossbreed of Anglo Nubian with PE, and the second main clade contains only Nigerian dwarf goat. A total of 3 hypervariable sites were detected at 284th (T>C), 371st, (C>T) and 372nd (C>T) in some cyt b gene sequences of goat breeds in study and resulted into the change in amino acids from Isoleucine to Threonine at 284th and Phenylalanine to Serine at 371st & 372nd. Furthermore, 5 polymorphic sites, 5 number of mutations, and 8 number of haplotypes were found across all samples. Overall haplotype diversity and nucleotide diversity were 0.716 ±0.058 and 0.00251±0.00035, respectively. The revealed low genetic diversity among seven dairy goats breeds in Yogyakarta and Central Java, indicating a narrow genetic base and high genetic homogeneity which may reduce adaptability and increase extinction risk.